Tuberculosis: a resurgent disease in immunosuppressed patients - Nissapatorn, V.; Kuppusamy, I.; Josephine, F.P.; Jamaiah, I.; Rohela, M.; Khairul Anuar, A. (2006)
A total of 136 patients, 67 HIV, 69 diabetes mellitus (DM) with or without (+/-) end-stage renal disease (ESRD), were registered for tuberculosis treatment at the National Tuberculosis Center (NTBC) from May to December, 2003. Ages ranged from 21-78 years (median 57.7 years) in TB/DM patients, and 21-62 (mean 37.6 +/- 8.3 years) in TB/HIV patients. TB was significantly found in younger and single HIV patients, but in older and married DM patients (p<0.05). Male patients in both groups were strongly associated with TB, while females more commonly had TB with DM (p<0.05). The majority of these patients were Malays, unemployed, and resided in Kuala Lumpur territory; however, no statistically significant difference was found between the 2 groups. Smoking, IVDUs and hepatitis C virus (HCV) infection were more significantly found in TB/HIV patients and further analysis showed that pulmonary TB was strongly associated with HCV infection in these patients (p<0.05). Pulmonary TB (62; 89.9) was the most common type found in both groups and was a markedly more common disease location in TB/DM patients, while extrapulmonary TB (21; 31.3) and miliary TB (14; 21) were significantly higher in TB/HIV patients. Cough with or without sputum, fever and loss of appetite and/or weight were common clinical presentations in both groups. Nevertheless, fever (54; 80.6) and lymphadenopathy (17; 25.4) were significantly related to TB/HIV patients (p<0.05). Interestingly, the presence of BCG vaccination and positive tuberculin skin test were stronger in TB/HIV (27; 40.3) and TB/DM (20; 29) patients, respectively (p<0.05). Overall, regular 6-, 9- and 12-months' anti-tubercular therapy (ATT) were routine practice, and EHRZ+B6 was the most common regimen used. The highest percentage of patients with treatment success were in both groups with 6 months' ATT; however, a significantly higher percentage was found in TB/DM (24; 34.8) than TB/HIV (13; 19.4) (p<0.05). A success rate of 15 (21.7) was noted for TB/DM patients with 9 months' ATT, which was similar to both groups with the 12-month regimen. A higher percentage failure rate (lost to follow-up) was seen in TB/HIV (19; 28.4) patients. Nine patients were reported to have anti-tubercular-drug side-effects, such as drug-induced hepatitis, blurred vision, and skin rash. No cases of drug resistance or death were notified among these patients.